Quran learning innovation for persons with disabilities - autism at the International Islamic University Malaysia - Wan Nik, Wan Suraya; Muhammad Hafiz Bukhari, Mohd Khadari; Khalid, Nursyahidah; Kamal Bahri, Ahmad Muttaqin; Pg Hj Petra, Nur-Ashikin; Abu Bakar, Muhammad; Ahmad Nazri, Muhammad Naguib (INTI International University, 2025)
In today’s era of globalization, Quranic education has seen remarkable progress, particularly in Malaysia, where increasing attention is being given to the needs of Persons with Disabilities (PWD). Among these groups, individuals with Autism Spectrum Disorder (ASD) face unique challenges in accessing and mastering Quranic knowledge. Autism, or ASD, is a neurodevelopmental condition that affects an individual’s ability to communicate, interact socially, and learn effectively. These challenges are often compounded by sensory sensitivities, challenges in understanding abstract concepts, and limited access to resources or trained educators who are familiar with special education strategies. Beyond identifying these challenges, the study also aims to elucidate the benefits that innovative Quranic learning methods can offer autistic students. Innovations such as the integration of visual aids, interactive digital platforms, individualized education plans (IEPs), and the use of technology—including Artificial Intelligence (AI)—are explored as potential solutions. These approaches can help make Quranic learning more engaging, interactive, and suited to the diverse needs of autistic learners. For example, visual support and gamified learning modules can enhance memory retention and motivation, while AI-powered tools can provide personalized feedback and adapt to each student’s pace and learning style. The methodology employed in this research is qualitative, involving in-depth interviews with four experts in the fields of autism education and Quranic studies. These experts offer valuable insights into effective teaching strategies, the challenges faced by autistic students, and the potential of innovative tools to support sustainable Quranic learning. In addition to expert interviews, a comprehensive literature review is conducted, examining previous studies related to autism and Quranic education. Participant observation is employed concurrently during the face-to-face interview session using a checklist that was adopted and adapted to suit the milieu of the IIUM landscape as well as the interview questions conducted with the respondents. This triple approach ensures that the findings are grounded in both practical experience and established research, providing a holistic understanding of the topic. The anticipated outcome of this study is to contribute meaningful recommendations for educators, curriculum developers, and policymakers in the field of special education. By highlighting the necessity of customized and innovative Quranic learning models, the study advocates for greater inclusion of autistic students in religious education. Ultimately, it is hoped that the findings will not only benefit autistic students at IIUM but will also serve as a reference for other institutions seeking to enhance Quranic education for PWDs. The innovations proposed in this research warrant serious consideration to ensure that all students, regardless of ability, have equitable access to the spiritual and educational benefits of the Quran. difficulties with verbal and non-verbal communication, and the need for structured, predictable learning environments. As such, it is crucial to develop and implement specialized methods that cater to the distinct learning profiles of autistic individuals, ensuring they are not left behind in religious and spiritual education. This study is designed to address the educational needs of autistic PWDs, with a particular focus on students at the International Islamic University Malaysia (IIUM). The primary objective is to facilitate sustainable Quranic learning for autistic students through methods that are both easily accessible and tailored to their specific requirements. Recognizing that conventional teaching approaches may not be effective for this group, the research seeks to identify and analyze the barriers that autistic students at IIUM encounter in their pursuit of Quranic knowledge. These barriers may include difficulties in focusing during lessons,